STRUGGLING FOR SELF-RESPECT(A POWER RELATION ANALYSIS OF THE MAIN CHARACTERS IN THE FILM SCRIPT BABEL) - Muna indraprasta Pratiwi, - (2010)
Entitled Struggling for Self-respect (A Power Relation Analysis of the Main Characters of the Film Script "Babel"), the present paper concerns the textual analysis of Babel film script, written by Guillermo Ariaga, in a power relation framework with the employment of power theories. The analysis is directed to unveil how power is negotiated among the dominant and the submissive characters as evidenced in the text. Based on the findings, it is revealed that power relation between the both sides is constructed upon the continuity application of domination by the dominant towards its subordinate and it also can work vice versa. Power is manifested, mainly during conflicts, in the forms of mental violence which drops down the self-respect of a person. The analysis also shows that identity along with power relation works in a circle form distributed from the dominant to the submissive and go back to the dominant, and so on. Self-respect comes from the reflected outer identity. The power relation among dominant and submissive characters reflect how power is not an individual belonging but rather 'borrowed', exercised, and reflected by people who are fortunately have a change and/fight for it. This makes power is fluid in nature where it can be anywhere else from every side of the relation of individuals.